2022
DOI: 10.3389/fphar.2022.875330
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mutant Kirsten Rat Sarcoma Viral Oncogene Homolog in Non-Small Cell Lung Cancer: Current Difficulties, Integrative Treatments and Future Perspectives

Abstract: In the past few decades, several gene mutations, including the anaplastic lymphoma kinase, epidermal growth factor receptor, ROS proto-oncogene 1 and rat sarcoma viral oncogene homolog (RAS), have been discovered in non-small cell lung cancer (NSCLC). Kirsten rat sarcoma viral oncogene homolog (KRAS) is the isoform most frequently altered in RAS-mutated NSCLC cases. Due to the structural and biochemical characteristics of the KRAS protein, effective approaches to treating KRAS-mutant NSCLC still remain elusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 96 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…KRAS mutations are associated with treatment efficacy and prognosis in NSCLC ( Wood et al, 2016 ; Ferrer et al, 2018 ; Roman et al, 2018 ). Targeting KRAS variant has be shown to have potential treatment applications in NSCLC ( Ricciuti et al, 2016 ; Uras et al, 2020 ; Li J. X. et al, 2022 ). Notably, KRAS mutations are linked to immune therapy resistance in NSCLC patients ( Kim et al, 2017 ; Adderley et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…KRAS mutations are associated with treatment efficacy and prognosis in NSCLC ( Wood et al, 2016 ; Ferrer et al, 2018 ; Roman et al, 2018 ). Targeting KRAS variant has be shown to have potential treatment applications in NSCLC ( Ricciuti et al, 2016 ; Uras et al, 2020 ; Li J. X. et al, 2022 ). Notably, KRAS mutations are linked to immune therapy resistance in NSCLC patients ( Kim et al, 2017 ; Adderley et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…KRAS, a member of the RAS family of protooncogenes, has been associated with a range of high-grade malignancies. KRAS has been identified as the most frequently mutated gene in human cancers that is responsible for 30% of all human carcinomas [1][2][3][4]. Studies found that the mutant version of KRAS was presented in 90% of pancreatic cancers [5][6][7], and up to 40% of colorectal cancers [3].…”
Section: Introductionmentioning
confidence: 99%